1993
DOI: 10.1002/ijc.2910530504
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin‐1β and interleukin‐6 in hepatoblastoma

Abstract: Thrombocytosis and fever are frequent symptoms in children with hepatoblastoma. Interleukin-6 (IL-6) has been shown to mediate thrombocytosis and an acute-phase reaction including fever. We therefore investigated samples from 14 untreated patients with hepatoblastoma for this cytokine and in addition for interleukin-1 alpha (IL-1 alpha), interleukin-1 beta (IL-1 beta) and tumor necrosis factor-alpha (TNF-alpha), all of which are known to induce IL-6 production. High serum levels of IL-6 were only found in 3/14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The exact mechanism of this hematologic complication, however, remains unclear. Schweinitz et al [5] have suggested interleukin 6 (IL-6) to be one of the mediators showing that hepatoblastoma cells induce IL-6 production in surrounding fibroblasts and endothelial cells by virtue of the endogenous secretion of IL-1β. Recently, however, the major physiological regulator of thrombopoiesis has been purified as c-mpl ligand and termed thrombopoietin (TPO) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of this hematologic complication, however, remains unclear. Schweinitz et al [5] have suggested interleukin 6 (IL-6) to be one of the mediators showing that hepatoblastoma cells induce IL-6 production in surrounding fibroblasts and endothelial cells by virtue of the endogenous secretion of IL-1β. Recently, however, the major physiological regulator of thrombopoiesis has been purified as c-mpl ligand and termed thrombopoietin (TPO) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data indicated that a variety of proinflammatory cytokines, including IL-1␤, IL-6, and TNF-␣, were significantly elevated in the serum or within the liver of patients with hepatitis virus infection (19 -21), liver cancer (22), or alcoholic liver diseases (23)(24)(25)(26)(27). We hypothesized that these elevated proinflammatory cytokines (such as IL-1␤) may also regulate IFN signaling pathway and may be implicated in the IFN resistance.…”
mentioning
confidence: 99%
“…This discrepancy as compared with the other hepatoblastoma cells could be explained by the poorly differentiated phenotype of the HepT1 cells, which either inhibited HGF-SF secretion or bound large amounts of the factor, preventing its detection. We have shown that IL-6 is produced in hepatoblastomas by stromal cells under the influence of tumor-cell derived IL-1␤ (von Schweinitz et al, 1993), which was found to activate fibroblasts to secrete HGF-SF (Tamura et al, 1993). In our experiments, IL-1 could have been responsible in part for the activation of fibroblasts to produce the factor.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumor cell cultures were set up from fresh material of non-pre-treated hepatoblastomas, as described (von Schweinitz et al, 1993). Briefly, tumor pieces were finely minced and incubated with RPMI-1640 medium, 10% FCS and collagenase type B (200 U/ml; GIBCO) for 2 hr.…”
Section: Cell Culturesmentioning
confidence: 99%